2017
DOI: 10.1101/186528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An integrated analysis of the epigenetic, genetic, and transcriptional patterns associated with outcome across cancer types

Abstract: Successful treatment decisions in cancer depend on the accurate assessment of patient risk. To improve our understanding of the molecular alterations that underlie deadly malignancies, we analyzed genomic profiles from 33,036 solid tumors with known patient outcomes. Contrary to expectations, we find that mutations in cancer driver genes are almost never associated with patient survival time. In contrast, copy number changes in these same genes are broadly prognostic. Analysis of methylation, microRNA, mRNA, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Despite the conflicting in vitro data, MELK expression remains one of the strongest predictors of patient mortality in diverse cancer types ( Smith and Sheltzer, 2017 ). Additionally, MELK has been implicated in several other cancer-related processes, including cancer stem cell maintenance, chemotherapy resistance, anchorage-independent growth, and reactive oxygen species (ROS)-signaling ( Wang et al, 2014 ; Ganguly et al, 2014a ; Beke et al, 2015 ; Kim et al, 2015 ; Seong et al, 2016 ; Choi et al, 2011 ; Gu et al, 2013 ; Hebbard et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the conflicting in vitro data, MELK expression remains one of the strongest predictors of patient mortality in diverse cancer types ( Smith and Sheltzer, 2017 ). Additionally, MELK has been implicated in several other cancer-related processes, including cancer stem cell maintenance, chemotherapy resistance, anchorage-independent growth, and reactive oxygen species (ROS)-signaling ( Wang et al, 2014 ; Ganguly et al, 2014a ; Beke et al, 2015 ; Kim et al, 2015 ; Seong et al, 2016 ; Choi et al, 2011 ; Gu et al, 2013 ; Hebbard et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, rapid cell division in tumors is indicative of tissue de-differentiation and aggressive disease; therefore, most cell cycle-regulated genes are also associated with clinical outcome (17,46,47). We found that controlling for cell proliferation ablates the significance of MELK expression, suggesting that this link may explain its prognostic role in cancer.…”
Section: Discussionmentioning
confidence: 73%
“…If MELK plays no overt role in cancer biology, then why would MELK expression be linked with death from cancer? We note that MELK expression is cell cycleregulated, peaking in mitosis (4,45), and gene signatures that capture mitotic activity have been found to be prognostic in multiple cancer types (17,46,47). We therefore considered the possibility that, rather than functioning as an oncogene or a cancer dependency, MELK expression could report cell division within a tumor.…”
Section: The Association Between Melk Expression and Cancer Lethalitymentioning
confidence: 99%
See 2 more Smart Citations